Cu oxide/ZnO-based surfaces for a selective ethylene production from gas-phase CO2 electroconversion. (May 2019) - Merino-Garcia, Ivan; Albo, Jonathan; Solla-Gullón, Jose; Montiel, Vicente; Irabien, Angel
Highlights: Cu oxide/ZnO catalysts are developed for CO2 electroconversion into C2 H4 . A C2 H4 production rate = 487.9 μmol m −2 s −1 and a FE = 91.1% are achieved. A C2 H4 /CH4 production rate ratio up to 139 is reached at 7.5 mAcm −2 . The synergic effect between Zn and Cu favors the selectivity toward C2 H4 . Abstract: In this work, the application of Cu oxides/ZnO-based electrocatalytic surfaces for the continuous and selective gas-phase electroreduction of CO2 to ethylene in a filter-press type electrochemical cell is studied. The prepared catalytic materials are characterized by transmission electron microscopy, X-ray diffraction and X-ray photoelectron spectroscopy. Then, the Cu oxides/ZnO-based gas diffusion electrodes are electrochemically characterized by cyclic voltammetry and Tafel plot analyses. The ethylene formation rate and Faradaic efficiency are as high as 487.9 μmol m −2 s −1 and 91.1% when a current density of 7.5 mAcm −2 (-2.5 V vs. Ag/AgCl) is applied to the system, with an ethylene/methane production ratio of 139, showing a better performance than previous electrocatalytic systems for the production of ethylene from CO2 conversion. Consequently, the use of Cu oxides/ZnO-based electrocatalysts for gas-phase CO2 reduction is a step forward in the production of C2 products, such as ethylene.